Bond strength of endodontic sealers after intracanal surface pretreatment with CO2 laser - Fuad Jacob Abi Rached Junior; Aline Evangelista Souza-Gabriel; Manoel Damião Sousa-Neto; Yara Teresinha Correa Silva-Sousa (Revista Sul-Brasileira de Odontologia, 2013)
The aim of this study was to evaluate in vitro the bonding of AH Plus and Endofill sealers to intraradicular canal walls after different dentin surface treatments. Material and methods: Sixty canines were sectioned obtaining dentin discs with 4-mm thickness and were embedded in acrylic resin. The canals were prepared with diamond burs. The specimens were divided into two groups (n = 30): GI – AH Plus and GII – Endofill and were subdivided into three groups based on the dentin surface treatment (n = 10): A – distilled and deionized water (control), B – 17% EDTA, C – CO2 laser with 3W in continuous mode for 10s. The specimens were submitted to push out test in a universal testing machine. Results: Tukey test revealed that the IB (AH Plus/17% EDTA) (17.59 ± 6.04) and IC (AH Plus/CO2 laser) (21.69 ± 4.93) subgroups had the highest values, which were statistically similar between each other (p > 0.05) and different from the other subgroups (p < 0.05). IIC subgroup (Endofill/CO2 laser) (7.25 ± 1.59) had intermediate values, which were statistically similar to (p > 0.05) IA subgroup (AH Plus/water) (10.99 ± 2.63), IIA subgroup (Endofill/water) (3.16 ± 0.83) and IIB subgroup (Endofill/ 17% EDTA) (5.31 ± 3.61), which had the smallest values (p < 0.05). Conclusion: The treatment of superficial intracanal dentin with CO2 laser and EDTA favored the adhesion of AH Plus and Endofill sealers.